FAKTOR DETERMINAN TINGKAT PENDAPATAN MUSTAHIQ PENERIMA ZAKAT PRODUKTIF - Muhammad Fakhri Amir (IQTISHADUNA, 2019)
This study aims to determine the factors that influence the level of income of mustahiq earners of productive zakat from the National Amil Zakat Agency (BAZNAS). This research is a field research using a quantitative approach. The main data obtained from the distribution of questionnaires directly to the mustahiq who have received productive zakat from BAZNAS as many as 37 people by using probability sampling techniques. The dependent variable used in this study is income mustahiq, while the independent variable is the amount of zakat, business assistance, business duration, type of business and education. Based on the results of this study indicate that the amount of zakat, business assistance, length of business, type of business and education simultaneously affect the level of income mustahiq. But partially, only three factors, namely the amount of zakat, business assistance, and length of business that have a significant influence on mustahiq income, while the other two factors namely the type of business and education have no influence on mustahiq income.